On the festivalization or “festivalitis” in Mexico: Vive Latino and Corona Capital as contemporary manifestations of mestizophilia and anglophilia (Revista Argentina de Musicología, 2020)
This text problematizes the consolidation and consequences of the festivalization in Mexico by means of the analysis of two of its most representative music festivals: Vive Latino and Corona Capital, both held in Mexico City and managed by OCESA, the main company dedicated to public and massive entertainment in Mexico. From this, an analysis of the musical discourses and curatorial logic of both festivals is proposed, which are considered to reproduce the ideals of two of the main tendencies of cultural management in Mexico: mestizophilia and hispanophilia (the second incarnated by means of an anglophilia). Although apparently contradictory, the text proposes that both tendencies are part of a greater identity tension: a “neocreolism” that promotes discourses of modernization under paternalistic criteria, whether from the notion of “mestizaje”, embodied in a supposedly Latin musical identity, or from a “cosmopolitan” aspiration, which explicitly omits any local musical expression. Ultimately, both perspectives —implicitly or explicitly— omit multiple local musical expressions for considering them “non modern” with the intention of legitimizing their own aspirational discourse.
Keywords: Mexico; mestizophilia; anglophilia; Vive Latino; Corona Capital